16 Pharmacological Interventions for Sialorrhoea in Parkinson's Disease: A Systematic Review. (16th March 2021) - Reid, A; Smyth, C; Reid, J; Bailey, M
Abstract: Introduction: We looked at patients with Idiopathic Parkinson's disease and reviewed articles that used any pharmacological therapy to attempt to reduce the volume or burden of sialorrhoea. The control was patients on placebo or receiving usual best care. The primary outcome was symptom burden of sialorrhoea. Method: The review was registered on Prospero (CRD42016042470.) 7 electronic databases (MEDLINE, EMBASE, CINAHL, PsycINFO, Cochrane Central Register of Controlled Trials (CENTRAL), LILACS) were searched until April 2019 using search terms for sialorrhoea and Parkinson's disease. We additional searched through the last 6 years of abstracts from the International Movement Disorder Conference, Movement Disorder Society International Congress and World Parkinson's Congress. Hand searching was performed of published journals from the Movement Disorder Journal of the Movement Disorder Society and Neurology. Inclusion criteria included patients aged over 18; patients with a diagnosis of Idiopathic Parkinson's disease; patients with the complication of sialorrhoea and any pharmacological therapy aimed at reducing sialorrhoea. All articles were assessed for risk of bias independently by two assessors using the Cochrane risk of bias tool. Results: 7 articles were included from the 1, 015 screened citations. 3 studies used Botox B as an intervention with clear objective measures and low risk of bias. These studies did show a significant reduction in sialorrhoea however the largest study showed some reporting bias and the others had small numbers and a short follow up period. 1 study looked at Botox A which showed significant improvement in sialorrhoea but had short follow-up. Conclusion: Most studies have very small numbers and were followed up for only 1 month. There was significant heterogeneity in outcome measures but little evidence of significant harm from from the treatments studied. Overall, more robust evidence is required in order to achieve a gold standard in the treatment of sialorrhoea.